Comparing nitrite-limited and ammonium-limited anammox processes treating low-strength wastewater: Functional and population heterogeneity. (November 2020) - Liu, Wenru; Song, Jiajun; Wang, Jianfang; Wu, Peng; Shen, Yaoliang; Yang, Dianhai
Abstract: Biomass segregation between granules/biofilm and flocs is widespread in anammox-based processes. The segregation of biomass allows for easy control of processes stability. The goal of this study is to understand the biomass segregation in two anoxic anammox reactors respectively operated in nitrite-limited (RNO2 ) and ammonium-limited (RNH4 ) modes treating low-strength wastewater at 20 °C. Results showed that size-based biomass segregation was developed in both reactors. But the functional and population heterogeneity was more significant in the ammonium-limited anammox reactor. The activity and abundance of anammox bacteria in large granules were significantly higher than that in flocs under the ammonium-limited conditions. The large granules played a major role in nitrogen removal in RNH4 . By contrast, both large granules and small flocs contributed significantly to the nitrogen loss in the nitrite-limited anammox reactor, since a large number of anammox bacteria existed in both granules and flocs. Besides, a number of Nitrospira -like NOB were also detected in both anoxic anammox reactors, which primarily inhabited in flocs seemingly droved by the availability of oxygen. But the abundance of Nitrospira in RNH4 was much higher than that in RNO2 . All these results suggested that selective flocs removal would be necessary for RNH4 to improve its anammox performance but non-essential for RNO2 . The two anammox reactors shared the predominant anammox species with the closest relative to Ca. Brocadia sp. 40 (98%). Unexpectedly, the anammox species grew faster in RNH4 . But the microbial diversity and evenness was much greater in RNO2, suggesting its higher functional stability. Highlights: The ammonium-limited and nitrite-limited anammox reactors were compared. Anammox bacteria mainly enriched in granules, NOB preferred to live in flocs. Anammox bacteria grew faster in the ammonium-limited reactor. The nitrite-limited reactor possessed the higher microbial diversity and evenness.